2007
DOI: 10.1002/elps.200600574
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical staining and quantification of dihydrolipoamide dehydrogenase diaphorase activity using blue native PAGE

Abstract: Mammalian mitochondrial dihydrolipoamide dehydrogenase (DLDH, EC 1.8.1.4) catalyzes NAD(+)-dependent oxidation of dihydrolipoamide in vivo and can also act as a diaphorase catalyzing in vitro nicotinamide adenine dinucleotide (reduced form) (NADH)-dependent reduction of electron-accepting molecules such as ubiquinone and nitroblue tetrazolium (NBT). In this paper, we report a gel-based method for histochemical staining and quantification of DLDH diaphorase activity using blue native PAGE (BN-PAGE). Rat brain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…In T. brucei, dihydrolipoyl dehydrogenase, one of the four subunits of OGDC is shared between OGDC and the pyruvate dehydrogenase complex (16). Its activity was detected using the same approach in mammalian mitochondria, implying that this assay is not specific for complex I activity (49). Furthermore, using a nongradient BNE method, both complex I and dihydrolipoyl dehydrogenase protein were detected simultaneously on the same gel (50), suggesting that the gel-based method used to separate mt respiratory complexes could be critical.…”
Section: Discussionmentioning
confidence: 99%
“…In T. brucei, dihydrolipoyl dehydrogenase, one of the four subunits of OGDC is shared between OGDC and the pyruvate dehydrogenase complex (16). Its activity was detected using the same approach in mammalian mitochondria, implying that this assay is not specific for complex I activity (49). Furthermore, using a nongradient BNE method, both complex I and dihydrolipoyl dehydrogenase protein were detected simultaneously on the same gel (50), suggesting that the gel-based method used to separate mt respiratory complexes could be critical.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that the enzyme is adversely affected by nitrosylation (Yan et al, 2007) suggesting that this might be the case also in vivo. While no decline in dihydrolipoamide dehydrogenase protein levels is observed in normal aging of the brain, a compromised activity was seen in neurodegeneration including Alzheimer’s disease (Gibson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Complexes containing dihydrolipoamide dehydrogenase can also be detected on native gels using NADH and nitroblue tetrazolium as substrates (67). Indeed, immunoblotting of the 4 to 16% native gel with antidihydrolipoamide dehydrogenase (Tb11.01.8470) MAb 17 revealed a band at ϳ500 kDa, the same size as the NADH dehydrogenase activity band (Fig.…”
Section: Respiratory Complex I In Bloodstream T Bruceimentioning
confidence: 92%